(untitled) (Journal of Comparative & International Higher Education, 2022)
The integration of Information and Communication Technologies (ICTs) in education has brought dramatic modifications in the paradigms and methods practiced, particularly in the developed countries. In recent years, the exploitation of ICTs in teaching and learning of different subjects is being expanded in the developing countries too. This study has made an attempt to explore the opportunities and challenges of using ICTs in English language teaching (ELT) in school education in the developing country Nepal. The English language teachers and the students learning English from two different schools were the informants in the study, and interview and focus group discussion (FGD) were used as the research methods. The study concluded that ICTs were useful for the teachers and students in their teaching and learning activities for accessing learning resources, preparing and presenting their lesson and for conducting collaborative learning activities. However, it was found that the teachers and students were not satisfied with their utilization of ICTs in teaching and learning of English. Access to ICT tools, and the skills needed to use ICTs were the main problems for them in the integration of ICTs in English language teaching and learning. Therefore, these constraints need to be minimized to improve the integration of ICTs in ELT.